Evidence psychometric initial of the scale of self-efficacy for aging (EAEE) in peruvian elderly [Evidencias psicométricas iniciales de la escala de autoeficacia para envejecer (EAE) en adultos mayores peruanos] - Caycho-Rodríguez, Tomás (2018)
ABSTRACT The study examines the psychometric evidences of the Self-Efficacy Scale for Aging (EAEE) in a sample of 400 older adults (75.2% women and 24.8% men) from the city of Trujillo (Peru) with an average age of 73.37 years (DE = 7.86). The participants completed the EAEE along with measures of life satisfaction and depression. The exploratory factor analysis (AFE) revealed that the EAEE presented a one-dimensional factorial structure. The confirmatory factor analysis (CFA) showed that the one-dimensional model had an acceptable fit (S-Bχ2 = 54.02, df = 345 p = .001; S-Bχ2/df = 1.54; CFI = .97; RMSEA = .052 [IC90% .021, .078]; y SRMR = .049; AIC= 118.96) and an adequate reliability (ω = .88 [IC95% .84 – .91]; α = .88 [IC95%: .84 - .91]). EAEE scores correlated positively with satisfaction with life (r = .56, p< .01 [IC95%: .46, .79]) and negative with depression (r = -.48, p< .01 [IC95%: -.37, -.73]). The results suggest that the EAEE presents evidence of validity based on the internal structure, convergent and discriminant, as well as an adequate reliability.